2011
DOI: 10.1016/j.pepi.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

On the seismogenic increase of the ratio of the ULF geomagnetic field components

Abstract: Following the paper by Fraser-Smith et al. (1990), many scientists have focused their research on the ULF geomagnetic field pulsations in the hope of finding possible anomalous signals caused by the seismic activity. Thereafter, many papers have reported ULF geomagnetic field polarization ratio increases which have been claimed to be related to the occurrence of moderate and strong earthquakes. Even if there is no firm evidence of correlation between the polarization ratio increase and seismic events, these pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 44 publications
3
63
0
Order By: Relevance
“…The presumed precursors of the Guam earthquake can be essentially reassumed in the increase of the fractal dimension of the geomagnetic field components and in the change of the ratio between the integrated power, in a fixed frequency band, of the vertical component and the horizontal components of the geomagnetic field, the so-called polarization ratio. However, recently Masci (2010Masci ( , 2011a and Thomas et al (2009b) have demonstrated that these presumed precursors of the Guam earthquake were normal disturbances closely related to changes of the global geomagnetic level and then not induced by the seismic activity. Ida et al (2005), hereafter cited as IDA, performed multifractal detrended fluctuation analysis (MFDFA) of ULF geomagnetic field data from the Guam observatory which is located 65 km away from the epicentre of the 1993 Guam earthquake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presumed precursors of the Guam earthquake can be essentially reassumed in the increase of the fractal dimension of the geomagnetic field components and in the change of the ratio between the integrated power, in a fixed frequency band, of the vertical component and the horizontal components of the geomagnetic field, the so-called polarization ratio. However, recently Masci (2010Masci ( , 2011a and Thomas et al (2009b) have demonstrated that these presumed precursors of the Guam earthquake were normal disturbances closely related to changes of the global geomagnetic level and then not induced by the seismic activity. Ida et al (2005), hereafter cited as IDA, performed multifractal detrended fluctuation analysis (MFDFA) of ULF geomagnetic field data from the Guam observatory which is located 65 km away from the epicentre of the 1993 Guam earthquake.…”
Section: Discussionmentioning
confidence: 99%
“…They excluded any correlation between the changes of the geomagnetic field multi-fractal parameters and the geomagnetic activity since the presumed multi-fractal precursors occurred during a geomagnetic quiet period. This is an oversimplified assumption since we must not consider the level of the geomagnetic activity but its variations which induce changes in several magnetic parameters as well as in the fractal characteristics of the geomagnetic field (see also Masci 2010Masci , 2011a. Figure 1 shows the time series of the MFDFA parameters reported by IDA as daily and 9-day running average values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, we should also not expect that in an observation site, (e.g. L'Aquila), a close correspondence between K p and the standardized polarization exists during a long time range (see Masci, 2011a). In brief, as claimed by Masci (2011b), the main issue is: a close correspondence between changes of an ULF geomagnetic field parameter (in this case the standardized polarization) and K p indicates that these changes are part of normal global geomagnetic field variations driven by solar-terrestrial interaction.…”
Section: Comments and Conclusionmentioning
confidence: 99%
“…Obviously, it is likely that an anomalous variation of a geomagnetic field parameter may be observed before the occurrence of an earthquake, but relating the anomaly with the seismic event without further validations is just an oversimplified conclusion. As a consequence, some authors (see Campbell, 2009;Thomas et al, 2009;Masci, 2010Masci, , 2011a have recently put into question well-known magnetic seismogenic precursors by showing that these anomalous signals are actually induced by normal geomagnetic activity. Prattes et al (2011), hereafter cited as P11, report the analysis of ULF magnetic data coming from the South European Geomagnetic Array (SEGMA) during the period [2008][2009].…”
Section: Introductionmentioning
confidence: 99%